Is Orius sauteri Poppius a Promising Biological Control Agent for Walnut Aphids? An Assessment from the Laboratory to Field - Ting Wang; Ping Zhang; Chenyang Ma; Muhammad Yasir Ali; Guizhen Gao; Zhaozhi Lu; Myron P. Zalucki (Insects, 2021)
Walnut aphids are major pests of walnut production with few commercially available natural enemies. We conducted laboratory and field experiments to evaluate the potential of Orius sauteri Poppius (Anthocoridae), a predatory bug, as a biological control agent against two walnut aphid species: the dusky-veined aphid (Panaphis juglandis Goeze) and the walnut aphid (Chromaphis juglandicola Kaltenbach). Both species co-occur on walnut trees; P. juglandis is distributed on the upper surface (adaxial) of leaves while C. juglandicola is found on the lower surface (abaxial) of leaves. Based on functional response experiments, O sauteri had a strong capacity for consuming both aphid species. Biocontrol efficacy of O. sauteri for each species in the laboratory and field experiments was high, 77% for P. juglandis and 80% for C. juglandicola, regardless if one or two predators being present. However, biocontrol efficacy declined 15–25% for C. juglandicola and 20–50% for P. juglandis when both aphid species were present on the same leaf. The efficacy of O. sauteri under (semi)-field conditions gave similar findings based on the percentage reduction of aphids and change in population growth rates of aphids. The reduced biocontrol efficacy of the predatory bug against mixed species populations of aphids can be explained by competition between the aphid species and differences in their preferred location on leaves. Our experiments showed that O. sauteri is a promising biocontrol agent, but biocontrol efficacy may decline when both aphid species are present on walnut trees. This should be considered in the commercial release of O. sauteri in walnut orchards to promote economic and environmental benefits of walnuts production.